Dynamical Behavior of a Delayed Holling Type-II Predator-Prey Model with Predator Cannibalism - Lavanya, R.; Vinoth, S.; Sathiyanathan, K.; Njitacke Tabekoueng, Zeric; Hammachukiattikul, P.; Vadivel, R. (Journal of Mathematics, 2022)
In this article, we propose the Holling type-II predator-prey model involving cannibalism and gestation delay in predators. We study the existence of all possible equilibrium points of the proposed model. We give the condition for the local stability and Hopf bifurcation analysis for the nondelayed model. Next, we also establish the local stability and Hopf bifurcation analysis for the corresponding delayed model. Finally, we discuss how cannibalism and delay play an important role in stabilizing and destabilizing the proposed system both theoretically and numerically.